Utilization of Clay as Adsorbent Laboratory Waste - Catherina M.Bijang; Ivonne Telussa (Hasanuddin University, 2008)
Treatment for laboratorium waste need to carry out for prevented environment pollution if accumulation occured in the world. Natural resources available in maluku like clay can used to treat heavy metal Pb and Cu wastes. This adsorben were clay from Ouw village in Saparua,Maluku. The clay were brown and black. Each clay were activated with soaked in sulfuric acid for 5 and 10 hours. The result showed that the black clay with activated for 5 hours in sulfuric acid had the best adsorb.This clay more effective for adsorp Pb2+ ion compare with Cu2+ ion.Keywords : clay, adsorben, heavy metal.